Clinical results of arthroscopic polyglycolic acid sheet patch graft for irreparable rotator cuff tears - Yu Mochizuki; Mitsuo Ochi (Elsevier, 2015)
The high retear rates after surgery for irreparable rotator cuff tears can be explained by the healing capacity potential of tendons and the native rotator cuff enthesis characterised by complex morphological structures, called direct insertion. Many experimental researches have focused on biologically augmenting the rotator cuff reconstruction and improving tendon-bone healing of the rotator cuff. The results of the experimental study showed that the polyglycolic acid sheet scaffold material allows for the regeneration of not only tendon-to-tendon, but also tendon-to-bone interface in an animal model. We performed a clinical study of the arthroscopic polyglycolic acid sheet patch graft used for the repair of irreparable rotator cuff tears. One-year clinical results of the repair of irreparable rotator cuff tears by arthroscopic patch graft with a polyglycolic acid sheet demonstrated improved shoulder function and a significantly lower retear rate, compared with patients treated with a fascia lata patch.